A mixed multiscale FEM for the eddy current problem with T, Φ-Φ and vector hysteresis. Issue 3 (18th January 2022) - Hanser, Valentin; Schöbinger, Markus; Hollaus, Karl
Abstract : Purpose: This work introduces an efficient and accurate technique to solve the eddy current problem in laminated iron cores considering vector hysteresis. Design/methodology/approach: The mixed multiscale finite element method based on the based on the T, Φ-Φ formulation, with the current vector potential T and the magnetic scalar potential Φ allows the laminated core to be modelled as a single homogeneous block. This means that the individual sheets do not have to be resolved, which saves a lot of computing time and reduces the demands on the computer system enormously. Findings: As a representative numerical example, a single-phase transformer with 4, 20 and 184 sheets is simulated with great success. The eddy current losses of the simulation using the standard finite element method and the simulation using the mixed multiscale finite element method agree very well and the required simulation time is tremendously reduced. Originality/value: The vector Preisach model is used to account for vector hysteresis and is integrated into the mixed multiscale finite element method for the first time.